Library anxiety its relationship to computer anxiety and library use among freshman students of De La Salle University-Dasmariñas in Cavite - Caraballa, Jerome M. (2010)
A visit to the library may prove to be an inevitable activity to a college student whether he may like it or not. It is because, library use among students is an essential part in any student's life to succeed not only in school but also in our society. Of course, not all students are properly equipped with all the knowledge especially when using a library that exhibits state-of-the-art facilities, like the one in De La Salle University - Dasmarinas, Cavite. The Aklatang Emilio Aguinaldo, as the library is called, housed and ever-expanding collection of books, journals, magazine, videos, CD-ROMS and all sorts of instructional materials. Its computers can access the World Wide Web and has its own Online Public Access Catalog (OPAC) System. All of this may be a bit overwhelming to a student, especially to a freshman, when he feels like he is not capable of handling such information. He becomes apprehensive in using the library and all of its facilities and related services like computers and such. This is called library anxiety.